Implementation of Labor Recruitment: A Case Study in Pasirranji Village Bekasi Regency - Megga Amelia Putri Putri; Dadan Kurniansyah; Nidaul Muthmainnah (NeoRespublica : Jurnal Ilmu Pemerintahan, 2026)
This study aims to analyze the implementation of labor recruitment in Pasirranji Village, Bekasi Regency. The study was motivated by the ongoing issues in the implementation of labor recruitment, such as transparency of information and coordination among the parties involved. This study employs a qualitative approach using the case study method. Data were collected through observation, interviews, and documentation, and were then analyzed using George C. Edward III’s policy implementation theory, which encompasses communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of labor recruitment has proceeded fairly well, though it is not yet fully optimal. The findings indicate that coordination among stakeholders still needs to be strengthened, particularly in conveying information to the public and implementing more transparent recruitment mechanisms. Additionally, the absence of a joint standard operating procedure (SOP) has led to differing interpretations in the implementation of recruitment. Nevertheless, the Pasirranji Village Government, Karang Taruna, and the Department of Labor have supported the implementation of local labor recruitment. The implications of this study are the need to develop joint SOPs, improve coordination among parties, and enhance information transparency so that the implementation of labor recruitment becomes more effective, accountable, and in accordance with applicable regulations.